The Genetic and Molecular Mechanisms of Congenital Hyperinsulinism - Galcheva, Sonya; Demirbilek, Hüseyin; Al-Khawaga, Sara; Hussain, Khalid (Frontiers in Endocrinology, 2019)
Congenital hyperinsulinism (CHI) is a heterogenous and complex disorder in which unregulated insulin secretion from pancreatic beta-cells leads to hyperinsulinaemic hypoglycaemia. The severity of hypoglycaemia varies depending on the underlying molecular mechanism and genetic defects. The genetic and molecular causes of CHI include defects in pivotal pathways regulating the secretion of insulin from the β-cell. Broadly these genetic defects leading to unregulated insulin secretion can be grouped into four main categories. The first group consists of defects in the pancreatic KATP channel genes (ABCC8 and KCNJ11). Genetic defects in these genes leads to the most severe forms of hypoglycemia. The second and third categories of conditions are enzymatic defects (such as GDH, GCK, HADH) and defects in transcription factors (for example HNF 1A, HNF 4A) leading to changes in nutrient flux into metabolic pathways which converge on insulin secretion. Lastly, a large number of genetic syndromes are now linked to hyperinsulinaemic hypoglycaemia. Over the last a few years there have been tremendous advances at the genetic and molecular levels in understanding the mechanisms that lead to unregulated insulin secretion from the β-cell. This review, therefore aims to provide up-to-date knowledge on these genetic and molecular mechanisms advances that lead to CHI.